The relation between age at menopause and age at first childbirth - Šťastná, Anna; Kocourková, Jiřina (Casopis lekaru ceskych, 2024)
Analysis of data from the representative "GGP - Contemporary Czech Family Survey" (2020-2022) on the population of women aged 40-69 years showed that the age of onset of menopause is associated with a low age at the birth of the first child. Women who had their first child before their 20th birthday, a pattern of reproductive behaviour common among generations of women before 1989, have an earlier onset of menopause than older first-time mothers. Conversely, the effect of higher age at first birth (35 years or more) on the delay of menopause has not been proved. However, this issue requires further investigation, as the sample analysed suggests certain tendencies. A larger sample size would be needed to make a conclusive finding.
Keywords: senioři; menopauza; Menopause; menopause, age at menopause, age at first birth; těhotenství; Česká republika; Middle Aged; Adult; Czech Republic; věk matky; věkové faktory; ženské pohlaví; Humans; Pregnancy; lidé středního věku; Age Factors; dospělí; Female; Aged; lidé; Maternal Age